Recursos sociais, investimento profissional e formas de consagração da psicologia em Aracaju/SE - Brandini, Mirela Provinciali (2012)
This dissertation analyses the career of psychologists working in a management position at different area of activities of the Psychology in the city of Aracaju/SE, and try to understand the social resources (academic, economic, political, religious, social origin, original position, social relations and professional and social status), which are mobilized by these professionals since their entry and rise in the professional market, besides of permanency in the managerial jobs such important to professional success. The interest appeared from the curiosity to investigate this group, based in the fact that is a predominantly individualistic profession, and so, has created some questions to be answered: a) what are the working areas of psychologists? b) How they rise to higher hierarchical levels in different areas of activities? c) How their academic and job career contributed to hold such prominent posts? The social resources were used as indicators to stand and explain the question. The empirical universe is provided by psychologist holding manager positions at psychology working area. This dissertation is divided in four moments: the first of them leaded the theoretical and conceptual model around the institutionalization of psychology profession, social resources and trajectory and its interrelations; the second investigated and treated the social conditions with the emergence and establishment of the profession of psychology in Brazil and Sergipe; the third presented and discussed the sociography of the psychology in Brazil based on two Brazilian researches; and the fourth demonstrated the career of the agents inside of a social composition analysis, academic life, the investment and professional perception and aimed to comprehend the request of social resources. This work explained that the request of social and cultural resources fundamentally burden to assume managerial posts and the use of these resources to assure the integration, permanency and rising to higher professional levels. The way as those resources were required is related to network relations, and were established and articulated directly by the agents or through their families, teachers and classmates. The period when these resources were triggered started at the university entrance. Cultural capital has its basis in the university degree (diploma), technical knowledge, expertise in the area and others important titles, however, the graduation is mandatory and essential to the professional insertion. To have an entrepreneur, persuasive and active posture is also very important to assume privileged positions. In regard of professional involvement and commitment, what cares is to be registered in the Psychology Council, to be involved with social work groups and engaged with both study groups and specific associations within more than one professional area of activity and working. It was in fact perceived that social networks were generated, established and maintained along the carrier of the agents.